Analisis Kecelakaan Kerja Menggunakan Metode Fault Tree Analysis (FTA) Pada Pelaksanaan Konstruksi Pembangunan Industri Makanan Di Kabupaten Gresik - Wibisono, R Endro; Hardaningrum, Farida; Palupi, Doni Ndito (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2024)
Work accidents are something that often happens on construction projects and deserve attention. The most difficult thing is to determine the root of the problem. The method used in this research is to look for the causes of work accidents, namely the Fault Tree Analysis (FTA) method. The FTA method is one way to resolve cases when failure or undesirable things occur by looking for the root of the problem from the basic events that arise and is described from each indication of the incident. This is done by identifying the relationship between causal factors and displaying it in the form of a fault tree which involves a simple logical "tree". Accidents are calculated for every 1,000,000 working hours of the worker's total "hours worked". The safe T value is a measurement that aims to compare the results of the level of accident reduction achieved for that work. The research results show that work accidents have an effect on work productivity. As a result of data processing and analysis, it was found that the occupational safety and health implementation program at PT. Sejahtera Asia Mulia can be said to have been implemented quite well. The accidents that occurred in 2020-2022 were 16, 13 and 7 accidents. The frequency level from 2020-2022 is 101.59; 71.15; 29.76. The severity level that occurred in 2020-2022 was 4844.44; 3409.96; 1785.71. Safe T value in 2021 is known to be -0.427 and in 2022 was -1.390. The decreasing rate of accidents and the severity of accidents from year to year indicates an increase in labor productivity.